PRINCIPLES OF ISLAMIC BUSINESS ETHICS IN ONLINE BUSINESS: A SHARIA COMPLIANCE FRAMEWORK AND SCORECARD FOR E-COMMERCE PLATFORMS - Mariana, Mariana (Fakultas Agama Islam Universitas Islam Al-Azhar, 2025)
The growth of e-commerce in Indonesia has propelled the digital economy, reaching a market value of 62 billion in 2024. However, ethical challenges such as fraud, lack of price transparency, and consumer rights violations undermine trust and contravene sharia principles. This study proposes a Sharia-Compliant E-Commerce Ethics Framework, integrating tauhid, equilibrium, free will, responsibility, and ihsan with digital trust metrics, and a Sharia Compliance Scorecard to quantitatively evaluate sellers. Developed through a synthesis of Islamic business ethics, digital trust theory, and behavioral economics, the framework is tested via a Tokopedia fraud case and validated with a hypothetical Shopee scenario to demonstrate scalability. The study evaluates the rights and obligations of buyers, sellers, and platforms, offering solutions like sharia-based seller certification, consumer education, and national regulatory guidelines. This approach minimizes fraud, fosters a fair and sharia-compliant business ecosystem, and enhances trust and customer loyalty, contributing academically through a novel framework and practically through measurable evaluation tools